Integrated Design and Control of Renewable Energy Sources for Energy Management - Krishna, T. V.; Maharana, M. K.; Panigrahi, C. K. (Engineering, Technology & Applied Science Research, 2020)
Growing population and expanding industry set off the demand for electrical energy and issues, such as the problem of peak load demand, emerge. To balance the supply and load demand problem, the energy management system has the vital role of Electric Peak shaving with the integration of microgrid into the utility grid. The combination of demand-side management with storable energy sources helps us resolve the matters concerned with the peak load demand. However, in a microgrid, whenever the distributed energy sources are interconnected, the DC bus link voltage will vary due to the inherent behavior of each source as they mainly depend on geographical conditions. This work proposes voltage droop control strategy to keep the DC bus link voltage at a constant value. Also, it gives an overlook of the present power sector scenario of India and a reassessment of the demand side management system and how it is utilized in electrical peak shaving.